Management of Radix Entomolaris of Mandibular First Molar With Complex Root Canal Curvatures: A Case Report and Mini Review - Ali Chamani; Maryam Gharechahi; Reza Shakiba; Farshad Alipour (Clinical Case Reports)
ABSTRACT Radix entomolaris (RE) characterized by an extra root in mandibular molars is a rare phenotype. When this condition coincides with complex root canal curvatures or S‐shaped canals, root canal therapy (RCT) challenges arise. The present study presents three cases of RE along with complex root curvatures. The challenges of RCT and case management in this study are addressed within the framework of paying attention to the access cavity according to the extra root, instrumentation with the crown‐down technique, sufficient irrigation, using nickel–titanium rotary systems, dense obturation with the warm vertical technique, and patient follow‐up. Also, in the last case, the management of two broken files by loop and bypass techniques is described. Adequate knowledge of the root canal system's morphology and the use of appropriate techniques and materials for root canal therapy are the background for successful RCT.